Acute Oral Toxicity Study of Paris polyphylla extract in Rats - Acharya BalKrishna; Hemanth Kumar Manikyam; Vinay K Sharma; Niti Sharma (International Journal of Phytomedicine, 2015)
Paris polyphylla Smith is regarded as “Wonder Herb” due to its vast therapeutic applications ranging from diarrhea to cancer. The cytotoxic effect of the rhizome extract on the healthy rats was monitored over a period of time. The extract proved non cytotoxic as animals gained weight and no signs of mortality, ill health or overt toxicity were observed. A brief period of dullness indicates a possible role of the extract in neuro-suppression. The cutoff median lethal dose (LD50) of extract after single oral administration to female rats, observed over a period of 14 days is found to be greater than 5000 mg/Kg body weight. Thus it can be used in the treatment of neurological disorders associated with hyper active neurons. Moreover as the extract is cytotoxic to cancerous cells only it would prove good target for future studies on anti cancer drugs. The results of this study collectively specify that oral administration of Paris polyphylla is not connected with any toxicologically significant effects and the data could provide satisfactory preclinical evidence of safety to launch a clinical trial on a standardized formulation of the plant extracts.